معتقل تفلفال النسوي بالاوراس أثناء الثورة الجزائرية 1955 /1962 من خلال الرواية الشفوية وشهادات المعتقلات - بن زروال, جمعة (جامعة الوادي University of Eloued, 2017)
تتناول هذه الورقة البحثية دور الرواية في كتابة التاريخ الشفوي للمرأة من خلال نماذج من شهادات النساء المعتقلات في السجون الفرنسية أثناء الثورة الجزائرية 1954 /1962، معتمدين في هذه الدراسة علي معتقلات سجن تفلفال النسوي بالاوراس الذي يعتبر أول معتقل للنساء في الجزائر أثناء الثورة التحريرية والذي تأسس سنة 1955 وخصص لسجن زوجات المجاهدين . اعتمدنا في دراستنا علي عدة نقاط أهمها: - دراسة نماذج من شهادات النساء المعتقلات مع أطفالهن في سجن تفلفال ، بسرد ظروف وأسباب الاعتقال والحياة اليومية داخل المعتقل وأساليب التعذيب الجسدية والنفسية التي تتعرض لها المعتقلات . - استقراء بعض الشهادات لمعتقلات سجن تفلفال النسوي مثل / شهادة ذهبية عبيد الله ، وشهادة الشامخة بن رحمون ، وشهادة جمعة سليماني....أكثر من عشرين امرأة معتقلة . - تحليل ومقارنة هذه الشهادات الشفوية بإبراز مدي مصداقيتها التاريخية من خلال الوثائق الأرشيفية والمصادر المكتوبة. - إبراز معاناة المرأة الريفية البسيطة ومدي تحملها مسؤولية الثورة مع أخيها الرجل من اجل تحرير وطنها . ملخص باللغة الانجليزية : This paper deals with the role of testimony in writing the oral history of women, through models of detainees testimonies of women in French prisons during the Algerian revolution 1954/1962, Relying in this study on the detainees of Tifelfel prison in Aures which is the first prison for women in Algeria during the revolution, which was founded in 1955 and was provided to detain the wives mujahideen. - Definition of women’s jail of Tifelfel addressing the causes and circumstances of its founding in 1955 by the French colonialism, and the motives behind its allocation to the wives of Mujahideen and rebels. - Study models of women detainees testimonies with their children in the prison of Tifelfel, listing the circumstances and reasons for the detention and daily life inside the prison and methods of physical and psychological torture suffered by detainees. - Extrapolate some testimonies of women detainnees in women’s prison of Tifelfel Example / the testimony of Dhehbiya Obaidullah, the testimony of Achamkha Ben Rahmon, and the testimony of Djemaa Soleimani .... More than twenty women detained.
Keywords: معتقل تفلفال، الثورة الجزائرية، المعتقلات